Halogen-free flame-retardant polyamide composition with low outgassing and high CTI value, and preparation method and application thereof

CN122878748APending Publication Date: 2026-10-09GUANGDONG TAISU NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611285219.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而该技术方案虽然具有良好的阻燃性,但CTI仅能达到600V,随着新能源汽车、光伏、电子电器工业的迅速发展,高电压继电器、高压连接器等器件对CTI提出了更高要求,600V仅能达到门槛需求,CTI≥800V的高CTI阻燃聚酰胺材料是目前聚酰胺改性的重要方向

Benefits of technology

1、本发明的阻燃剂为硅铝改性二乙基次膦酸铝,在制备过程过程中,有机硅氧烷和铝醇盐先通过水解缩合在二乙基次膦酸铝表面生长硅铝纳米颗粒,随后铝钛复合偶联剂中的铝氧基团和钛氧基团与硅铝纳米颗粒表面的羟基发生反应,长链基团覆盖在硅铝纳米颗粒表面,制备的阻燃剂在具有低析出性的同时还有效提高了聚酰胺组合物的CTI。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of polyamides, and particularly relates to a halogen-free flame-retardant polyamide composition with low emission and high CTI value, a preparation method and application thereof. The halogen-free flame-retardant polyamide composition with low emission and high CTI value comprises the following components in parts by weight: polyamide resin 40-60 parts, flame retardant 3-7 parts, synergist 2-5 parts, glass fiber 15-25 parts, lubricant 0.5-1.5 parts, and antioxidant 0.2-1 part. The flame retardant is aluminum diethyl phosphinate modified with silicon and aluminum. The synergist is illite coated with silane modified rosin acid. The halogen-free flame-retardant polyamide composition with low emission and high CTI value provided by the application can achieve a flame-retardant grade of 0.8mm V-0, CTI>800V, and tensile strength>150MPa. After a double 85 test for 1000h, there is no emission, and CTI is greater than or equal to 800V.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polyamide technology, specifically relating to a halogen-free flame-retardant polyamide composition with low precipitation and high CTI value, its preparation method, and its application. Background Technology

[0002] Polyamides have occupied an important position in the field of engineering plastics for many years due to their excellent physical and chemical properties.

[0003] Traditional flame-retardant polyamides typically rely on the synergistic effect of halogenated flame retardants and antimony trioxide. While this results in significant flame retardancy, antimony trioxide degrades the material's resistance to electrical tracking. To address this issue, the applicant's previous research, as disclosed in Chinese Patent Publication No. CN122427459A, outlines a high CTI value brominated flame retardant composite composition, its preparation method, and its application. This high CTI value brominated flame retardant composite composition comprises a brominated flame retardant, a flame retardant synergist, and a CTI enhancer. The flame retardant synergist includes modified pyrophyllite powder and modified zinc-magnesium nanocomposite; the CTI enhancer is zirconium silicate powder. Although this technical solution achieves a V-0 flame retardancy rating (0.4 mm), a CTI of 600V (3 mm), and a notched impact strength greater than 9 KJ / m² by using specific flame retardant synergists and CTI enhancers to prepare the brominated flame retardant, this solution demonstrates that the polyamide composite material achieves a flame retardancy rating of V-0 (0.4 mm), a CTI of 600V (3 mm), and a notched impact strength greater than 9 KJ / m². 2 At the same time, GWIT reaches 825℃ (1mm). However, brominated flame retardants may release toxic gases when burning, and halide ions are prone to interact with metal parts during long-term use, leading to corrosion of electrical equipment and affecting product life.

[0004] Halogen-free flame-retardant polyamides prepared using halogen-free flame retardants have the advantages of being environmentally friendly, non-toxic, and harmless. However, conventional halogen-free flame retardants have problems such as large polarity differences with polyamides, weak interfacial bonding, uneven dispersion in the matrix, and easy migration to the surface. This not only leads to stickiness and whitening of the surface, but also causes a decrease in flame retardant or mechanical properties.

[0005] Chinese Patent CN118290934A discloses a low-exudation, high-CTI, halogen-free flame-retardant high-temperature nylon composite material, comprising the following raw material components by weight percentage: 60-80 parts high-temperature resistant nylon, 5-40 parts fiber material, 5-15 parts coated aluminum diethylphosphinate, 5-15 parts bridging DOPO, 1-5 parts inorganic nano-synergist, 1-5 parts toughening agent, 0.5-2 parts lubricant, and 0.5-2 parts heat stabilizer. The fiber material is one or more of carbon fiber, glass fiber, basalt fiber, etc.; the coated aluminum diethylphosphinate is aluminum diethylphosphinate coated with heat-resistant coating materials such as silazane or siloxane; the inorganic nano-synergist is one or more of nano-montmorillonite, nano-attapulgite, nano-silica spheres, etc. However, although this technical solution has good flame retardancy, the CTI can only reach 600V. With the rapid development of new energy vehicles, photovoltaics, and the electronics industry, devices such as high-voltage relays and high-voltage connectors have put forward higher requirements for CTI. 600V can only meet the threshold requirements. High CTI flame-retardant polyamide materials with CTI≥800V are an important direction for polyamide modification. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings and deficiencies of the prior art and provide a halogen-free flame-retardant polyamide composition with low precipitation and high CTI value, its preparation method and application. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value provided by this invention can achieve a flame retardant rating of 0.8 mm V-0, CTI>800V, and tensile strength>150MPa; after 1000h of double 85 test: no precipitation phenomenon, CTI≥800V.

[0007] The objective of this invention can be achieved through the following methods: In a first aspect, the present invention provides a halogen-free flame-retardant polyamide composition with low precipitation and high CTI value, comprising the following components in parts by weight: 40-60 parts of polyamide resin, 3-7 parts of flame retardant, 2-5 parts of synergist, 15-25 parts of glass fiber, 0.5-1.5 parts of lubricant, and 0.2-1 parts of antioxidant; wherein the flame retardant is silica-alumina modified diethylphosphinic acid aluminum; and the synergist is rosin acid modified silane-coated illite.

[0008] Furthermore, the polyamide resin is selected from at least one of PA6 and PA66.

[0009] Furthermore, the preparation method of the flame retardant is as follows: aluminum diethylphosphonate is added to an aqueous ethanol solution, the pH is adjusted with an alkaline substance, organosiloxane and aluminum alkoxide are added first and stirred for reaction, then aluminum-titanium composite coupling agent is added and stirred for reaction, after the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the flame retardant.

[0010] Furthermore, the phosphorus content of the aluminum diethylphosphonate is ≥23%, and the D50 is ≤6µm.

[0011] Furthermore, the pH is adjusted to 8-9.5 using an alkaline substance.

[0012] Furthermore, the organosiloxane is selected from at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane.

[0013] Furthermore, the aluminum alkoxide is aluminum isopropoxide.

[0014] Furthermore, the mass ratio of the aluminum diethylphosphonate, organosiloxane, aluminum alkoxide, and aluminum-titanium composite coupling agent is 10:0.5-1:1-1.5:0.1-0.2.

[0015] Furthermore, the volume concentration of the ethanol aqueous solution is 90-95%.

[0016] Furthermore, the mass ratio of aluminum diethylphosphonate to the aqueous ethanol solution is 1:5-10.

[0017] Furthermore, the preparation method of the flame retardant is as follows: aluminum diethylphosphonate is added to an aqueous ethanol solution, the pH is adjusted with an alkaline substance, organosiloxane and aluminum alkoxide are added first and stirred at room temperature for 2-5 hours, then aluminum-titanium composite coupling agent is added and stirred at 40-50°C for 1-2 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the flame retardant.

[0018] Aluminum diethylphosphinate is a highly efficient halogen-free flame retardant with excellent thermal stability and minimal impact on the mechanical and electrical properties of flame-retardant composites. It is widely used in polyamide materials. However, it has two significant problems: firstly, it is prone to thermal decomposition during processing, leading to a decrease in flame retardancy; secondly, it is prone to precipitation in humid and hot environments, especially ultrafine aluminum diethylphosphinate, which is more likely to agglomerate and precipitate due to its smaller particle size.

[0019] To address this technical problem, this invention creatively employs silicon-aluminum modification. During the modification process, organosiloxanes and aluminum alkoxides first grow silicon-aluminum nanoparticles on the surface of aluminum diethylphosphinate through hydrolysis and condensation. These silicon-aluminum nanoparticles not only possess excellent heat resistance and effectively protect aluminum diethylphosphinate during processing, but they also inhibit the development of carbon traces, thereby improving the CTI of the polyamide composition. Subsequently, the aluminum and titanium groups in the aluminum-titanium composite coupling agent react with the hydroxyl groups on the surface of the silicon-aluminum nanoparticles, and long-chain groups cover the surface of the silicon-aluminum nanoparticles. This improves the dispersibility of aluminum diethylphosphinate in the polyamide while reducing its surface energy. It also improves the low precipitation properties of aluminum diethylphosphinate while accelerating the rolling off of conductive droplets and shortening the arc discharge time, thereby improving the CTI of the polyamide composition.

[0020] Furthermore, the preparation method of the rosin acid modified silane is as follows: rosin acid, epoxy silane, tetrabutylammonium bromide and acetone are mixed, heated and reacted, and the acetone is removed after the reaction is completed to obtain the product.

[0021] Further, the epoxy silane is selected from at least one of 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0022] Furthermore, the molar ratio of the rosin acid and the epoxysilane is 1:1-2.

[0023] Furthermore, the amount of tetrabutylammonium bromide added is 0.5-1.5% of the total mass of rosin acid and epoxy silane.

[0024] Furthermore, the amount of acetone added is 3-5 times the mass of rosin acid.

[0025] Furthermore, the conditions for the heating reaction are: temperature 30-50℃, time 4-6h.

[0026] Furthermore, the preparation method of the synergist is as follows: illite is dispersed in an aqueous ethanol solution, rosin acid-modified silane is added and stirred for reaction, after the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the synergist.

[0027] Furthermore, the mass ratio of illite, aqueous ethanol solution, and rosin acid-modified silane is 1:5-10:0.05-0.1.

[0028] Furthermore, the preparation method of the synergist is as follows: illite is dispersed in an ethanol aqueous solution, rosin acid modified silane is added and stirred at 60-80℃ for 3-6 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the final product.

[0029] The present invention aims to provide a high CTI flame-retardant polyamide material with a CTI ≥ 800V. The inventors have found that the CTI of polyamide compositions obtained by using conventional synergists such as alumina cannot reach ≥ 800V, and the CTI will decrease significantly after damp heat treatment.

[0030] To solve this technical problem, this invention creatively employs rosin acid-modified silane to coat illite. The layered structure of illite can form a physical barrier in the polyamide matrix, which not only blocks the extension of the carbonization path during tracking and improves the CTI of the polyamide composition, but also increases the diffusion path and time of water molecules, thereby improving the resistance of the polyamide composition to damp heat. The rosin acid-modified silane structure not only has hydrophobic long siloxane molecular chains, but also has the unique hydrophobic hydrogenated phenanthrene ring structure of rosin acid. By coating illite with rosin acid-modified silane and adding it to the polyamide composition, it can work together with flame retardants to improve the hydrophobicity of the polyamide composition, thereby making the CTI of the polyamide composition ≥ 800V before and after damp heat treatment.

[0031] Furthermore, the glass fiber has a diameter of 8-15 μm and a length of 1-5 mm.

[0032] Furthermore, the lubricant is selected from at least one of zinc stearate, calcium stearate, pentaerythritol stearate, ethylene bis-stearamide, and polyethylene wax.

[0033] Furthermore, the antioxidant is selected from at least one of antioxidant 168, antioxidant 1010, and antioxidant 1098.

[0034] Secondly, the present invention provides a method for preparing a halogen-free flame-retardant polyamide composition with low precipitation and high CTI value, comprising the following steps: fully mixing polyamide resin with flame retardant, synergist, lubricant and antioxidant, and feeding it into a twin-screw extruder through the main feed port; adding glass fiber through the side feed port; and then blending and granulating to obtain the final product.

[0035] Thirdly, the present invention provides an application of a halogen-free flame-retardant polyamide composition with low precipitation and high CTI value in new energy electric vehicles.

[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. The flame retardant of the present invention is silicon-aluminum modified diethylphosphinate. In the preparation process, organosiloxane and aluminum alkoxide first grow silicon-aluminum nanoparticles on the surface of diethylphosphinate through hydrolysis and condensation. Subsequently, the aluminum oxygen group and titanium oxygen group in the aluminum-titanium composite coupling agent react with the hydroxyl groups on the surface of the silicon-aluminum nanoparticles, and the long-chain groups cover the surface of the silicon-aluminum nanoparticles. The prepared flame retardant has low exudation and also effectively improves the CTI of the polyamide composition.

[0037] 2. The synergist of the present invention is illite coated with rosin acid-modified silane. When added to the polyamide composition, it can not only block the extension of the carbonization path during the tracking process, but also work together with the flame retardant to improve the hydrophobicity of the polyamide composition, thereby making the CTI of the polyamide composition ≥ 800V before and after wet heat treatment.

[0038] 3. The halogen-free flame-retardant polyamide composition with low exudation and high CTI value provided by the present invention can achieve a flame retardant rating of 0.8 mm V-0, CTI>800V, and tensile strength>150MPa; after 1000h of double 85 test: no exudation phenomenon, CTI≥800V. Detailed Implementation

[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] Unless otherwise specified in the examples and comparative examples, the conditions were performed under standard conditions or conditions recommended by the manufacturer. All reagents and instruments used were commercially available products unless otherwise specified.

[0041] Example 1 This example provides a halogen-free flame-retardant polyamide composition with low exudation and high CTI value, comprising the following components in parts by weight: 40 parts polyamide resin, 3 parts flame retardant, 5 parts synergist, 15 parts glass fiber, 0.5 parts lubricant, and 0.3 parts antioxidant.

[0042] The polyamide resin is PA6 with a relative viscosity of 2.45. It is sourced from Guangdong Hengshenmeida New Material Co., Ltd., and its model number is M2400.

[0043] The specific preparation method of the flame retardant is as follows: aluminum diethylphosphonate is added to an ethanol aqueous solution (volume concentration of 95%), the pH is adjusted to 8.5 using an alkaline substance, γ-aminopropyltriethoxysilane and aluminum isopropoxide are added first and stirred at room temperature for 3 hours, then aluminum-titanium composite coupling agent is added and stirred at 40°C for 2 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the flame retardant.

[0044] The mass ratio of aluminum diethylphosphonate, γ-aminopropyltriethoxysilane, aluminum isopropoxide, and aluminum-titanium composite coupling agent is 10:0.6:1.2:0.15.

[0045] The aluminum diethylphosphonate has a phosphorus content of ≥23% and a D50 of ≤6µm. It is sourced from Zhejiang Xusen Flame Retardant Co., Ltd., model: XS-FR-T315.

[0046] The aluminum-titanium composite coupling agent is sourced from Nanjing Jingtianwei Chemical Co., Ltd., model number: JTW-1618.

[0047] The mass ratio of aluminum diethylphosphinate to the aqueous ethanol solution is 1:10.

[0048] The preparation method of the synergist is as follows: illite is dispersed in an ethanol aqueous solution (volume concentration of 90%), rosin acid modified silane is added and stirred at 70°C for 5 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the synergist.

[0049] The mass ratio of illite, ethanol aqueous solution and rosin acid modified silane is 1:8:0.08.

[0050] The illite has a particle size of 3.1 ± 1 μm.

[0051] The preparation method of the rosin acid modified silane is as follows: rosin acid, 3-glycidoxypropyltrimethoxysilane, tetrabutylammonium bromide and acetone are mixed and heated at 45°C for 5 hours. After the reaction is completed, the acetone is removed to obtain the silane.

[0052] The molar ratio of rosin acid and 3-glycidoxypropyltrimethoxysilane is 1:1.2.

[0053] The amount of tetrabutylammonium bromide added is 1% of the total mass of rosin acid and epoxy silane.

[0054] The amount of acetone added is 4 times the mass of rosin acid.

[0055] The glass fiber has a diameter of 10μm and a length of 3mm, and is sourced from China Jushi Co., Ltd., model number: ECS10-03-568H.

[0056] The lubricant is calcium stearate.

[0057] The antioxidants are antioxidant 168 and antioxidant 1010 in a mass ratio of 1:1.

[0058] The preparation method of the above-mentioned halogen-free flame-retardant polyamide composition with low precipitation and high CTI value includes the following steps: the polyamide resin is fully mixed with flame retardant, synergist, lubricant and antioxidant and fed into a twin-screw extruder through the main feed port, and glass fiber is added through the side feed port. After blending and granulation, the product is obtained.

[0059] Example 2 This example provides a halogen-free flame-retardant polyamide composition with low exudation and high CTI value. The only difference from Example 1 is that it includes the following components in parts by weight: 50 parts polyamide resin, 5 parts flame retardant, 3 parts synergist, 20 parts glass fiber, 1 part lubricant, and 0.5 parts antioxidant; all other components are the same.

[0060] Example 3 This example provides a halogen-free flame-retardant polyamide composition with low exudation and high CTI value. The only difference from Example 1 is that it includes the following components in parts by weight: 60 parts polyamide resin, 7 parts flame retardant, 2 parts synergist, 25 parts glass fiber, 1.5 parts lubricant, and 1 part antioxidant; all other components are the same.

[0061] Comparative Example 1 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that the preparation method of the flame retardant is as follows: aluminum diethylphosphinic acid is added to an aqueous ethanol solution (volume concentration of 95%), the pH is adjusted to 8.5 using an alkaline substance, γ-aminopropyltriethoxysilane is added, and the mixture is stirred and reacted at room temperature for 3 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed, and dried to obtain the final product.

[0062] The mass ratio of aluminum diethylphosphinic acid to γ-aminopropyltriethoxysilane is 10:0.6; all other aspects are the same.

[0063] Comparative Example 2 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that the preparation method of the flame retardant is as follows: aluminum diethylphosphinic acid is added to an aqueous ethanol solution (volume concentration of 95%), the pH is adjusted to 8.5 using an alkaline substance, γ-aminopropyltriethoxysilane is added and stirred at room temperature for 3 hours, then an aluminum-titanium composite coupling agent is added and stirred at 40°C for 2 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed, and dried to obtain the final product.

[0064] The mass ratio of aluminum diethylphosphonate, γ-aminopropyltriethoxysilane, and aluminum-titanium composite coupling agent is 10:0.6:0.15; all other components are the same.

[0065] Comparative Example 3 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that the preparation method of the flame retardant is as follows: aluminum diethylphosphinate is added to an ethanol aqueous solution (volume concentration of 95%), the pH is adjusted to 8.5 using an alkaline substance, aluminum isopropoxide is added and stirred at room temperature for 3 hours, then an aluminum-titanium composite coupling agent is added and stirred at 40°C for 2 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed, and dried to obtain the final product.

[0066] The mass ratio of aluminum diethylphosphonate, aluminum isopropoxide, and aluminum-titanium composite coupling agent is 10:1.2:0.15; all other components are the same.

[0067] Comparative Example 4 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that the preparation method of the flame retardant is as follows: aluminum diethylphosphinic acid is added to an aqueous ethanol solution (volume concentration of 95%), the pH is adjusted to 8.5 using an alkaline substance, γ-aminopropyltriethoxysilane and aluminum isopropoxide are added first and stirred at room temperature for 3 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the final product.

[0068] The mass ratio of aluminum diethylphosphinic acid, γ-aminopropyltriethoxysilane, and aluminum isopropoxide is 10:0.6:1.2; all other components are the same.

[0069] Comparative Example 5 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that the synergist is alumina with a particle size of 50 μm; all other aspects are the same.

[0070] Comparative Example 6 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that the synergist is illite; all other aspects are the same.

[0071] Comparative Example 7 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that the preparation method of the synergist is as follows: illite is dispersed in an ethanol aqueous solution (volume concentration of 90%), 3-glycidoxypropyltrimethoxysilane is added, and the mixture is stirred at 70°C for 5 hours. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed, and dried to obtain the final product. The mass ratio of illite, ethanol aqueous solution, and 3-glycidoxypropyltrimethoxysilane is 1:8:0.08; all other aspects are the same.

[0072] Comparative Example 8 provides a halogen-free flame-retardant polyamide composition, which differs from Example 2 only in that it includes the following components in parts by weight: 50 parts polyamide resin, 5 parts flame retardant, 3 parts synergist, 20 parts glass fiber, 1.5 parts silicone powder, 1 part lubricant, and 0.5 parts antioxidant; all other components are the same.

[0073] The synergist is illite, and the silicone powder is sourced from Xingbeda (Shanghai) Chemical Materials Co., Ltd., model ST-LS100; all other components are the same.

[0074] Performance testing: The halogen-free flame-retardant polyamide compositions prepared in the above examples and comparative examples were subjected to the following performance tests.

[0075] 1. Flame retardancy: Test sample size: 125mm×13.0mm×0.8mm, tested according to UL-94 standard.

[0076] 2. CTI: Test sample size: 60mm×60mm×3mm, tested according to IEC 60112 standard.

[0077] 3. Resistance to damp heat: Test sample size: 60mm×60mm×3mm, placed in a constant temperature and humidity chamber, placed at 85℃ and 85% relative humidity for 1000h, observe whether white spots appear and test CTI.

[0078] 4. Tensile strength: Tested in accordance with GB / T 1040.1-2025 Determination of tensile properties of plastics - Part 1: General rules.

[0079]

[0080] As shown in Table 1, in Examples 1-3, the flame retardants were added to PA6 at a ratio of 7.5-12%, and the prepared halogen-free flame-retardant polyamide compositions achieved a flame retardancy rating of 0.8 mm V-0, CTI ≥ 800 V, and tensile strength > 150 MPa. After 1000 hours of the double 85 test, no precipitation was observed, and CTI ≥ 800 V. In Comparative Example 1, the flame retardant did not contain aluminum isopropoxide or aluminum-titanium composite coupling agent during preparation, and the flame retardancy, CTI, and tensile strength of the prepared halogen-free flame-retardant polyamide composition decreased significantly. After 1000 hours of the double 85 test, precipitation was observed, and the CTI decreased significantly.

[0081] In Comparative Example 2, no aluminum isopropoxide was added during the preparation of the flame retardant. The flame retardancy and CTI of the prepared halogen-free flame-retardant polyamide composition decreased significantly. After 1000 hours of double 85 test, the CTI decreased significantly.

[0082] In Comparative Example 3, no organosiloxane was added during the preparation of the flame retardant. The flame retardancy, CTI, and tensile strength of the prepared halogen-free flame-retardant polyamide composition decreased significantly. After 1000 hours of the double 85 test, precipitation was observed, and the CTI decreased significantly.

[0083] In Comparative Example 4, no aluminum-titanium composite coupling agent was added during the preparation of the flame retardant. The CTI and tensile strength of the prepared halogen-free flame-retardant polyamide composition decreased significantly. After 1000 hours of the double 85 test, precipitation was observed, and the CTI decreased significantly.

[0084] The synergists for Comparative Examples 5 and 6 were conventional alumina and illite. The CTI of the prepared halogen-free flame-retardant polyamide compositions decreased significantly, and the CTI decreased significantly after 1000 h of the double 85 test.

[0085] In Comparative Example 7, the synergist was modified using only epoxy silane during the preparation process, and the CTI of the prepared halogen-free flame-retardant polyamide composition decreased significantly. After 1000 hours of the double 85 test, the CTI decreased significantly.

[0086] The synergist of Comparative Example 8 was illite, and conventional low surface energy material silicone powder was added. The CTI of the prepared halogen-free flame-retardant polyamide composition decreased significantly, and the CTI decreased significantly after 1000 hours of double 85 test.

[0087] Comparative Examples 1-4 show that the silicon-aluminum modified diethylphosphinic acid aluminum prepared in this invention has excellent flame retardancy and resistance to damp heat. It is not easy to precipitate, and at the same time, the halogen-free flame-retardant polyamide composition also has resistance to tracking. Comparative Examples 5-8 show that the illite-coated illite with rosin acid-modified silane, prepared in this invention, significantly improves the resistance to tracking and damp heat in the halogen-free flame-retardant polyamide compositions.

[0088] The halogen-free flame-retardant polyamide composition provided by this invention can meet the needs of high-voltage relays, high-voltage connectors and other devices in the fields of new energy vehicles, photovoltaics, and electronic and electrical industries.

[0089] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A halogen-free flame-retardant polyamide composition with low exudation and high CTI value, characterized in that, The product comprises the following components in parts by weight: 40-60 parts polyamide resin, 3-7 parts flame retardant, 2-5 parts synergist, 15-25 parts glass fiber, 0.5-1.5 parts lubricant, and 0.2-1 parts antioxidant; wherein the flame retardant is silicon-aluminum modified diethylphosphinic acid aluminum; and the synergist is rosin acid modified silane-coated illite.

2. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to claim 1, characterized in that, The polyamide resin is selected from at least one of PA6 and PA66.

3. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to claim 1, characterized in that, The flame retardant is prepared as follows: aluminum diethylphosphonate is added to an aqueous ethanol solution, the pH is adjusted with an alkaline substance, organosiloxane and aluminum alkoxide are added and stirred for reaction, then aluminum-titanium composite coupling agent is added and stirred for reaction. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the flame retardant.

4. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to claim 3, characterized in that, The organosiloxane is selected from at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; the aluminum alkoxide is aluminum isopropoxide.

5. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to any one of claims 1-4, characterized in that, The preparation method of the rosin acid modified silane is as follows: rosin acid, epoxy silane, tetrabutylammonium bromide and acetone are mixed and heated to react. After the reaction is completed, the acetone is removed to obtain the silane.

6. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to claim 5, characterized in that, The preparation method of the synergist is as follows: illite is dispersed in an aqueous ethanol solution, rosin acid-modified silane is added and stirred to react. After the stirring reaction is completed, the mixture is filtered, the precipitate is collected, the precipitate is washed and dried to obtain the synergist.

7. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to claim 6, characterized in that, The glass fiber has a diameter of 8-15 μm and a length of 1-5 mm.

8. The halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to claim 7, characterized in that, The lubricant is selected from at least one of zinc stearate, calcium stearate, pentaerythritol stearate, ethylene bis-stearamide, and polyethylene wax; the antioxidant is selected from at least one of antioxidant 168, antioxidant 1010, and antioxidant 1098.

9. A method for preparing the halogen-free flame-retardant polyamide composition with low precipitation and high CTI value according to any one of claims 1-8, characterized in that, The process includes the following steps: Polyamide resin is thoroughly mixed with flame retardant, synergist, lubricant and antioxidant, and then fed into a twin-screw extruder through the main feed port. Glass fiber is added through the side feed port. The mixture is then blended and granulated to obtain the final product.

10. The application of the low-exudation, high-CTI-value halogen-free flame-retardant polyamide composition according to any one of claims 1-8 in new energy electric vehicles.

Citation Information

Patent Citations

  • Low-precipitation, high-CTI, halogen-free and flame-retardant high-temperature nylon composite material and preparation method thereof

    CN118290934A

  • Brominated flame retardant compound composition with high CTI (comparative tracking index) value as well as preparation method and application of brominated flame retardant compound composition

    CN122427459A